Immunostimulatory, Antibacterial and antibiofilm activity of purified Donkey colostrums lactoferrin on multidrug resistance Serratia liquefaciens producing Intl gene - Mahdi, Likaa, H.; Zaki, Neihaya, H.; Salman, Istabreq, M. A.; Zwain, Luma, A. H. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: Modern methods of biofilm prevention depended on the utilize of normal foodstuffs can solve antibacterial and antibiofilm problems.Objective: To purify donkey lactoferrin, and evaluate antibiotic resisted Serratia liquefaciens which producing Intl gene and investigate the inhibitory action of lactoferrin on biofilm and stimulate immune response.Methods: lactoferrin extracted from donkey milk, and purified by ammonium sulfate and Sephadex chromatography. Antibacterial and antibiofilm activities of lactoferrin on Serratia liquefaciens were assayed, and effect of lactoferrin on the innate immune response of mice was determined.Results: Lactoferrin contains 9.88% carbohydrates, 128 ppm iron, and molecular weight was 85kDa. It reduced S.liquifaciens in lung tissues of mice, and TNF-α and IL-6 cytokine levels decreasing by oral uptake of donkey milk.Conclusion: All isolates resistance to Amoxicillin-clavulanic acid, and Intl gene was 160 bp. Lactoferrin concentration was about 2.77mg/ml. lactoferrin increase innate immune response from S. liquefaciens infection. These outcomes can be evidence for the way to original comprehensions regarding the use of Donkey colostrums lactoferrin as an oral adjuvant for a wide range of diseases.